Macondo: Property and tragedies - Arribas Irazola, Guillermo (2014)
Property involves the possibility for men tocontrol their surroundings. Part of this control involves  the  exclusion of others from the benefits produced by their controlled goods.The possibility to exclude or not to excludeothers allows or prevents an efficient use of goods. So the tragedy of the commons ariseswhen there are no rights of exclusion; and the tragedy of anticommons, where there is anexcess of exclusion rights.In this article, the author makes a complete analysis of the tragedy of commons and anticommons, in relation with property rights, pointing out the differences and similarities between both of them, their presence in everyday life and their relevance in our legal system.